2007
DOI: 10.1016/j.brainres.2006.10.052
|View full text |Cite
|
Sign up to set email alerts
|

An ERP study of syntactic processing in English and nonsense sentences

Abstract: The timecourse of the interaction between syntactic and semantic information during sentence processing in monolingual native English speakers was investigated using event-related potentials (ERPs). To examine the effects of semantic information on syntactic processing, the results for normal English sentences were compared to those for semantically impoverished nonsense (Jabberwocky) sentences. Within each sentence type condition, half of the sentences contained a syntactic violation. Violations elicited a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 59 publications
7
42
0
Order By: Relevance
“…Critically, however, when there is no clear alternative to which the flawed input could be corrected, no P600 component is observed, as in the case of the "classical" semantic anomalies (31), or in Jabberwocky materials in which plausibility cues are absent (e.g., ref. 41). In some cases in which a correction is unlikely, a P600 has nonetheless been reported (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, however, when there is no clear alternative to which the flawed input could be corrected, no P600 component is observed, as in the case of the "classical" semantic anomalies (31), or in Jabberwocky materials in which plausibility cues are absent (e.g., ref. 41). In some cases in which a correction is unlikely, a P600 has nonetheless been reported (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an anterior negativity which is more bilateral in distribution (e.g., Friederici & Frisch, 2000; Friederici & Meyer, 2004; Friederici, et al, 1993; Frisch, Hahne, & Friederici, 2004; Hagoort, et al, 2003; Hahne, 2001; Hahne & Friederici, 1999, 2002; Hahne & Jescheniak, 2001; Münte, et al, 1997; Rossi, et al, 2006; Yamada & Neville, 2007; Ye, Luo, Friederici, & Zhou, 2006). To date no theory of language processing has sought to address the functional significance of these differences in distribution, although the question has been identified as an important one for future research (Hahne & Friederici, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One of these is a negative-going wave, typically larger over left anterior electrode sites between 100-500 ms, known as the left anterior negativity (LAN). The LAN has been elicited by a variety of syntactic violation types, such as phrase structure violations (Friederici, et al, 1993; Gunter, Friederici, & Hahne, 1999; Hahne & Friederici, 1999; Neville, Nicol, Barss, Forster, & Garrett, 1991; Yamada & Neville, 2007) and morphosyntactic violations (Coulson, King, & Kutas, 1998a; Friederici, et al, 1993; Münte, Heinze, & Mangun, 1993). The LAN typically occurs in one or both of two time windows (100-300 ms and 300-500 ms), which has lead some researchers to propose the existence of two distinct, separate components, with the first, termed the early left anterior negativity (ELAN), indexing processes different from those indexed by the second, LAN (Friederici, 1995; Friederici & Mecklinger, 1996; Hahne & Jescheniak, 2001).…”
Section: Erp Studies Of Language Processingmentioning
confidence: 99%
“…Some research suggested that this component is primarily elicited by the inclusion of a grammaticality judgment task (Kuperberg, 2003, Yamada & Neville, 2007), or a monitoring process triggered by a conflict, e.g. when an unexpected linguistic item is encountered where another item is highly expected (Kolk et al, 2003).…”
Section: Introductionmentioning
confidence: 99%